COMMERCIAL CARCASS PIECES OF MALE BALINES DUCK (anas platyrhynchos) THAT GIVEN INDIGOFERA (Indigofera zollingeriana) LEAF JUICE IN DRINKING WATER - N. F., Ismia; Siti, N. W.; Ardika, I N. (Jurnal Peternakan Tropika, 2022)
Bali duck ( Anasplatyrhinchos ) is one type of poultry that has the potential as a supplier of animal needs in Indonesia, apart from chicken. However, the productivity is still low, so it is necessary to make efforts to increase the productivity of Bali duck ( Anasplatyrhinchos ), one of which is by improving the quality and quantity of feed consumed.This study aims to determine the effect of giving indigofera leaf juice in drinking water on commercial carcass pieces of male balines duck aged eight weeks and has beed carried out for eight weeks at Teaching Farm Faculty of Animal Husbandry, Udayana University, Bali.  The design of this study is a completely randomized design (CRD), wich consists 4 treathments and 5 replications, each replications consist of 6 ducks, so there are 120 male balines ducks aged two weeks.  The four treatments were the level of indigofera leaf juice through drinking water is P 0 (control), P 1 (2%), P 2 (4%) dan P 3 (6%).  Variables observed is: slaughter weight, carcass weight, carcass percentage and percentage of commercial carcass in pieces (breast, thigh, back and wing).  The data obtained were analyzed using variance, if there were significant differences (P<0,05) then the analysis was continued with Duncan’s multiple distance test.  The result showed that the administration of indigofera leaf juice in drinking water has significant (P<0,05) on the slaughter weight, the carcass weight, the carcass percentage and the percentage of commercial carcass in pieces (breast, thigh, back and wing).  Based on the results of study it can be concluded that the administration of 2-6% indigofera leaf juice in drinking water can increase the percentage of carcasses of breast and thighs, but reduce the percentage of carcasses of back and wings of male balines duck aged eight weeks.   Keyword : male balines duck, indigofera leaf juice, commercial carcass pieces